Retained guidewire following the use of the straight end of Seldinger guidewire for hemodialysis catheterization - Tanmoy Ghatak; Neeraj Kumar; Ratender K Singh (Wolters Kluwer -Medknow Publications, 2024)
Renal replacement therapy for kidney diseases usually requires hemodialysis catheterization. In literature, loss of a guidewire into the circulation is reported and this complication is preventable if appropriate measures are being used. This case report is of a 21-year-old female, who presented with intermittent fever and had dengue shock syndrome and acute kidney injury. A failed attempt to introduce a hemodialysis catheter of the right internal jugular vein was reported at some other hospitals. Using ultrasonography, X-rays, and computed tomography angiography of the neck, unraveling and guidewire loss were revealed. An unraveled Seldinger guidewire was removed after neck exploration. Migration of the guide in the central vein was revealed after puncturing the vascular wall. After surgical retrieval, the location of the retained guidewire revealed that the straight end of the Seldinger guidewire might have been used during catheterization. Proper training, skill-based learning, and early recognition of the signs of retained Seldinger guidewire are of utmost priority.